The Relation of Viewing Intensity and Perception of Indosiar’s Bintang Pantura Talent Show Participant’s Personal Branding Performance Towards Public Impression of Dangdut Music Development among FISIP Undip’s Students - Wulan Ferra Safitri; Agus Naryoso, S.Sos, M.Si (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2016)
The background of this study is one of Indonesia TV station that serves Dangdut Pantura talent show program on the primetime period within 4 hours duration, 5 days a week. Will it gives any positive or not to dangdut music that already got a negative perception in Indonesia people’s mindset, that will make an effect to public impression about development of dangdut music. This study aims to analyze the relation of viewing intensity and perception of Indosiar’s Bintang Pantura talent show participant’s personal branding performance towards public impression of dangdut music development among Fisip Undip’s students. This study is a kind of explanatory study, that explain the connection between the variables. Population number of this study are 5.153 person, the sample number user got by using Frank Lynch formula are 97 person. Sample choosen by using probability sampling technique with proporsional random sampling method. Data collected by using self-administered survey (quesioner) technique, and using Rank Kendall analytic method. User used theory of finite effect of mass media to get know about the relation of viewing intensity of Indosiar's Bintang Pantura talent show among Fisip Undip’s students (X1) with public impression of dangdut music development among Fisip Undip’s students (Y). User used theory of interpersonal perceiption and public opinion to connected perception of Indosiar’s Bintang Pantura talent show participant’s personal branding performance among Fisip Undip’s students (X2) towards public impression of dangdut music development among Fisip Undip’s students (Y) . The study result showed : (1) There is a positive relation between viewing intensity of Indosiar's Bintang Pantura talent show among Fisip Undip’s students with public impression of dangdut music development among Fisip Undip’s students, it proved by the value of r (0,200) > r tabel (0,1996) and signification standard at 0,007 < 0,01. (2) There is a positive reason between perception of Indosiar’s Bintang Pantura talent show participant’s personal branding performance among Fisip Undip’s students towards public impression of dangdut music development among Fisip Undip’s students proved by the value of r (0,206) > r tabel (0,1996) and signification standard at 0,005 < 0,01.